2018
DOI: 10.1186/s12944-018-0750-4
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic on urine samples after α-lipoic acid and/or eicosapentaenoic acid supplementation in healthy overweight/obese women

Abstract: BackgroundEicosapentaenoic acid (EPA) and α-lipoic acid (α-LA) have been investigated for their beneficial effects on obesity and cardiovascular risk factors. In the current research, the goal was to evaluate metabolomic changes following the dietary supplementation of these two lipids, alone or combined in healthy overweight/obese sedentary women following an energy-restricted diet. For this purpose, an untargeted metabolomics approach was conducted on urine samples using liquid chromatography coupled with ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Out of these articles, four studies recognised significant effects of ALA supplementation on weight loss as compared with the placebo group, whereas changes in weight was not statistically significant in other studies. As for BMI, 6 studies reported a significant reduction in the ALA‐treated group compared with the placebo group, whereas changes in BMI were not statistically significant in other studies. Furthermore, significant reduction in WC was observed only two studies .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Out of these articles, four studies recognised significant effects of ALA supplementation on weight loss as compared with the placebo group, whereas changes in weight was not statistically significant in other studies. As for BMI, 6 studies reported a significant reduction in the ALA‐treated group compared with the placebo group, whereas changes in BMI were not statistically significant in other studies. Furthermore, significant reduction in WC was observed only two studies .…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, study by Masharani et al and Konrad et al because of low sample size were not included in this study. As a result, totally, 24 studies were included in the current systematic review and meta‐analysis, whereas 21, 18 and 11 studies were included in the meta‐analysis of the effects of ALA on BMI, weight and WC, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations